Regional and Developmental Differences in Na+ Currents in Vestibular Primary Afferent Neurons - Meredith, Frances L.; Rennie, Katherine J. (Frontiers in Cellular Neuroscience, 2018)
The vestibular system relays information about head position via afferent nerve fibers to the brain in the form of action potentials. Voltage-gated Na+ channels in vestibular afferents drive the initiation and propagation of action potentials, but their expression during postnatal development and their contributions to firing in diverse mature afferent populations are unknown. Electrophysiological techniques were used to determine Na+ channel subunit types in vestibular calyx-bearing afferents at different stages of postnatal development. We used whole cell patch clamp recordings in thin slices of gerbil crista neuroepithelium to investigate Na+ channels and firing patterns in central zone (CZ) and peripheral zone (PZ) afferents. PZ afferents are exclusively dimorphic, innervating type I and type II hair cells, whereas CZ afferents can form dimorphs or calyx-only terminals which innervate type I hair cells alone. All afferents expressed tetrodotoxin (TTX)-sensitive Na+ currents, but TTX-sensitivity varied with age. During the fourth postnatal week, 200–300 nM TTX completely blocked sodium currents in PZ and CZ calyces. By contrast, in immature calyces [postnatal day (P) 5–11], a small component of peak sodium current remained in 200 nM TTX. Application of 1 μM TTX, or Jingzhaotoxin-III plus 200 nM TTX, abolished sodium current in immature calyces, suggesting the transient expression of voltage-gated sodium channel 1.5 (Nav1.5) during development. A similar TTX-insensitive current was found in early postnatal crista hair cells (P5–9) and constituted approximately one third of the total sodium current. The Nav1.6 channel blocker, 4,9-anhydrotetrodotoxin, reduced a component of sodium current in immature and mature calyces. At 100 nM 4,9-anhydrotetrodotoxin, peak sodium current was reduced on average by 20% in P5–14 calyces, by 37% in mature dimorphic PZ calyces, but by less than 15% in mature CZ calyx-only terminals. In mature PZ calyces, action potentials became shorter and broader in the presence of 4,9-anhydrotetrodotoxin implicating a role for Nav1.6 channels in firing in dimorphic afferents.